Assessment of cardiac dysfunction in COVID-19 patients using layer-specific strain echocardiography in short-axis and long-axis views - Mengjiao Zhang; Jianxiong Chen; Lingheng Wu; Guiyang Xi; Xinyi Li; Lin Jin; Zhaojun Li (BMC Cardiovascular Disorders)
Abstract Objectives Cardiac dysfunction is commonly observed in COVID-19 patients, but its impact on different myocardial layers—endocardial, mid-myocardial, and epicardial remains insufficiently understood. This study aims to evaluate myocardial dysfunction in COVID-19 patients by assessing both the long-axis and short-axis function of the left ventricle (LV) using two-dimensional myocardial layer-specific strain imaging. Methods A total of 197 COVID-19 patients were enrolled and categorized into three subgroups: mild, moderate, and severe. Cardiac structural and functional indices, along with biomarker levels, were collected to analyze their correlation with global longitudinal strain (GLS) and global circumferential strain (GCS). Results GLS and GCS were reduced in moderate and severe COVID-19 patients, including layer-specific GLS and GCS (both p < 0.05). E/A ratio, left ventricular ejection fraction (LVEF), and myoglobin were identified as independent factors influencing GLS (all p < 0.05). Age, LVEF, cardiac troponin I (cTnI), and myoglobin were independent factors influencing GCS (p < 0.05). Furthermore, B-type Natriuretic Peptide (BNP) and myoglobin were identified as independent predictors of both GLS in the whole wall (GLSww) and endocardial (GLSendo), with β values of -0.22, -0.21 and -0.39, -3.70, respectively (all p < 0.05). GLS, including endocardial, mid-myocardial, and epicardial myocardial layers, demonstrated superior diagnostic performance compared to GCS, with AUC values of 0.81, 0.83, and 0.84 vs. 0.61, 0.57, and 0.55, respectively (all p < 0.001). Conclusion There are differences in myocardial injury caused by COVID-19 across different layers of the myocardium, both in the longitudinal and circumferential directions, with more pronounced damage observed in the inner myocardium. GLS demonstrated superior diagnostic performance compared to GCS in identifying myocardial dysfunction. Furthermore, myocardial dysfunction was correlated with blood pressure, myocardial structure, and biochemical markers.